EXPERIMENTALLY INVESTIGATION OF THE EFFECT OF A SQUARE CROSS-SECTIONAL OBSTACLE LOCATED IN A CHANNEL ON HEAT TRANSFER - Gul, Hasan; Evin, Duygu; Tanyildizi, Vedat (Yildiz Technical Univ, 2006)
In the present study, the effects of a square cross-sectional obstacle, located before the heated zone of a rectangular channel normal to the flow direction and parallel to the heated surface, on heat transfer and friction characteristics are investigated, experimentally. The experiments were conducted for Re number in the range of 3.10(3)<15.10(3). It was seen that, the size and location of the obstacle, which can be changed vertically and horizontally, affect heat transfer. Optimum parameters that cause maximum heat transfer enhancement were determined. 142 % heat transfer enhancement was obtained with the obstacle for optimum conditions while increase in friction factor was 200 %.
Keywords: Obstacle; heat transfer; flow